Differential privacy and membership inference attacks - Ong, Ting Yu (Nanyang Technological University, 2023)
The growing use of machine learning on various datasets results in privacy concerns about records of the data being leaked. Membership inference is a type of attack that identifies the members of the training dataset. The research studies a privacy-preserving mechanism, differential privacy, to mitigate membership inference attacks. Generally, there is a lack of studies that include the two mentioned concepts: membership inference and differential privacy. This research extends the concepts to the less-tested datasets to understand the interaction between the concepts. Image, Time Series and Natural Language Processing datasets were used to train the target models and the reference models. As expected, differential privacy does hinder the membership inference attack by reducing it to a random guess for Image Dataset. However, for the other types of data, there are no observable changes before and after the implementation of differential privacy. Hence, the implementation of differential privacy was able to maintain the attack at a random guess level, suggesting that implementing differential privacy can help to mitigate the membership inference attack.